Multiphase structure SrCo (1-x) NixO (3-delta) perovskite type OER catalytic material and preparation method thereof

By introducing excess Ni elements into the perovskite oxide catalyst, the Sr9Ni7O21 phase was formed, and the SrCo1-yNiyO3-δ/Sr9Ni7O21 composite material was prepared, which solved the problem of high overpotential in the existing catalysts in the OER reaction, and achieved a heterogeneous structured catalytic material with low electrochemical potential and high catalytic performance.

CN119640317APending Publication Date: 2025-03-18KUNMING UNIV OF SCI & TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411955376.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-28
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The existing perovskite oxide catalysts have problems with incomplete oxidation in the OER reaction, resulting in high overpotentials, limiting their application.

Method used

By introducing excess Ni elements into the SrCoO3-δ system, the Sr9Ni7O21 phase with high OER activity was formed by the sol-gel method, and the decomposition was prevented by setting a low annealing temperature to prevent it from decomposing. SrCo1-yNiyO3-δ/Sr9Ni7O21 composite material was prepared.

Benefits of technology

A multiphase structure SrCo1-xNixO3-δ perovskite-type high-performance OER catalytic material with low electrochemical potential in alkaline electrolytes is realized, which improves the catalytic performance and maintains the structural stability of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119640317A_ABST
    Figure CN119640317A_ABST
Patent Text Reader

Abstract

The invention discloses a SrCo < 1-x > Ni < x > O < 3-delta > perovskite type OER catalytic material with a multiphase structure and a preparation method thereof, and belongs to the field of catalysis. According to the invention, the principle of B-site doping in perovskite oxide is utilized, excessive Ni element is introduced into the SrCoO3-delta system through a sol-gel method, and the Sr9Ni7O21 phase with high OER activity is induced and formed through co-treatment of pre-calcination and annealing, and meanwhile, the decomposition of the Sr9Ni7O21 phase at high temperature is avoided due to relatively low annealing temperature. The SrCo < 1-x > Ni < x > O < 3-delta > / Sr < 9 > Ni < 7 > O < 21 > composite catalytic material prepared by the invention has excellent OER activity in an alkaline electrolyte, and the overpotential required for providing the current density of 10 mAcm <-2 > in a 1 mol / L KOH solution is only 321 mV. The preparation process is simple, the production cost is low, and help is provided for preparation of the non-noble metal-based composite OER catalytic material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a multi-phase structure of SrCo 1-x Ni x O 3-δ The invention relates to a perovskite-type OER catalytic material and a preparation method thereof, belonging to the field of catalysis. Background Art

[0002] Hydrogen is a pollution-free secondary energy with high calorific value. The development and application of hydrogen energy is expected to solve the energy crisis and climate change caused by excessive consumption of fossil fuels. Hydrogen (H 2 O→H 2 +1 / 2O 2 ) is one of the most promising methods. The oxygen evolution reaction (OER) is the limiting reaction at the anode in the water splitting system. Its complex intermediate steps involve multiple electron / proton transfers, and the kinetic process is slow. It also means that a considerable overpotential is required for the reaction to occur. Therefore, it is necessary to develop catalysts with high performance and long-term stability to realize the development and application of hydrogen energy.

[0003] Precious metal-based catalysts (IrO 2 , RuO 2 etc.) show excellent water oxidation performance, but their scarcity and high cost limit their large-scale application. Non-precious metal-based perovskite oxides have been widely studied due to their compositional flexibility and structural diversity. Isabela C. Man et al. calculated the ΔG of many theoretical perovskite oxides. 0 O* -ΔG 0 HO* , which was used as a descriptor of OER activity, predicted that cubic SrCoO 3 The low overpotential under alkaline conditions makes the Sr-Co-O system a model catalyst. However, in actual synthesis, there is a problem of incomplete oxidation. Only oxygen-deficient SrCoO with a hexagonal structure can be synthesized under normal pressure. 3-δ , and has an undesirable overpotential value.

[0004] There are mainly two improvement methods for the problems existing in the above system: one is to improve the electrochemical process on its surface by compounding with other active materials. This method has the characteristics of being more flexible, but the manufacturing process is complicated and not conducive to large-scale application. The second is to dope other elements at the A site or the B site to regulate its electronic state and phase structure, so as to obtain better catalytic activity. Although this method is simple to prepare, it has restrictions on the doping elements and doping amounts. Patent application CN110860292A uses the principle of perovskite B-site doping to obtain a cation co-doped perovskite catalyst, but the catalytic performance improvement brought about by the doping effect is limited, especially when the doping elements are Ni, Cu and other elements with large electronegativity. At the same time, the sample with the best catalyst performance prepared by it still has a high overpotential of 380mV. Summary of the invention

[0005] In view of the above technical problems, the present invention provides a multi-phase structure SrCo 1-x Ni x O 3-δ Perovskite-type high-performance OER catalytic material and its preparation method. Based on the B-site doping principle, a simple sol-gel method was used to prepare SrCoO 3-δ The introduction of excess Ni into the system induces the formation of Sr with high OER activity. 9 Ni 7 O 21 , SrCo with low overpotential was prepared 1-y Ni y O 3-δ / Sr 9 Ni 7 O 21 Composite material, and by setting a lower annealing temperature to increase Sr 9 Ni 7 O 21 Phase content.

[0006] To achieve the above purpose, the technical solution adopted by the present invention is: a multi-phase structure SrCo 1-x Ni x O 3-δ A method for preparing a perovskite-type high-performance OER catalytic material comprises the following steps:

[0007] (1) Weigh Sr(NO 3 ) 2 、Co(NO 3 ) 2 6H 2 O and Ni (NO 3 ) 2 6H 2 O, add water to dissolve to form a mixed solution and heat;

[0008] (2) After adding the complexing agent, ammonia water is added to adjust the pH of the solution to alkaline, and the water is evaporated by heating to obtain a gel; the gel is then vacuum dried, pre-calcined, and annealed to obtain SrCo 1-x Ni x O 3-δ catalyst.

[0009] As an embodiment of the present invention, the multiphase structure SrCo 1-x Ni x O 3-δ The preparation method of perovskite-type high-performance OER catalyst material uses Sr as A-site metal and Co as B-site metal, and uses sol-gel method to prepare SrCoO 3-δ Excess Ni is introduced into the system to form Sr with high OER activity. 9 Ni 7 O 21 phase, and avoid Sr by setting a lower annealing temperature 9 Ni 7 O 21 Phase decomposition, finally obtaining SrCo with oxygen vacancies 1-y Ni y O 3-δ / Sr 9 Ni 7 O 21 The composite catalyst, wherein y is 0.1-0.2, and δ is 0.2-0.5.

[0010] As an embodiment of the present invention, the Sr(NO 3 ) 2 、Co(NO 3 ) 2 6H 2 O and Ni (NO 3 ) 2 6H 2 O has a molar ratio of 1:1-x:x, 0.2≤x≤0.5, where Sr(NO 3 ) 2 、Co(NO 3 ) 2 6H 2 O and Ni (NO 3 ) 2 6H 2 When the molar ratio of O is 1:0.6:0.4, the prepared SrCo 1-x Ni x O 3-δ The catalyst has the best OER performance and the most stable structure.

[0011] As an embodiment of the present invention, the heating temperature in step (1) is 70-80° C., and the heating time is 20-30 min.

[0012] As an embodiment of the present invention, the complexing agents used in step (2) are ethylenediaminetetraacetic acid and citric acid, wherein the molar ratio of ethylenediaminetetraacetic acid and citric acid to total metal ions is (0.8-1.2):(1.8-2.2):1.

[0013] As an embodiment of the present invention, in step (2), the pH of the solution is adjusted to 7-9, the heating temperature is 110-120° C., and the heating time is 40-45 min.

[0014] As an embodiment of the present invention, the vacuum drying temperature in step (2) is 220-250°C, and the vacuum drying time is 5-6h; the pre-calcination temperature is 300-400°C, and the pre-calcination time is 2-3h, and the heating rate is 5°C / min.

[0015] As an embodiment of the present invention, the annealing temperature in step (2) is 950-1050°C for 5-6h, wherein when the annealing temperature is 950°C, SrCo 1-x Ni x O 3-δ The catalyst has the best OER performance and the most stable structure.

[0016] The present invention also claims the multi-phase structure SrCo 1-x Ni x O 3-δ Preparation method of perovskite-type high-performance OER catalyst material to prepare multiphase structure SrCo 1-x Ni x O 3-δ Perovskite-type high-performance OER catalytic materials.

[0017] As an embodiment of the present invention, the multiphase structure SrCo 1-x Ni x O 3-δ Perovskite-type high-performance OER catalytic materials include SrCo 1-y Ni y O 3-δ Phase, Sr 9 Ni 7 O 21 phase and NiO phase.

[0018] Compared with the prior art, the present invention has the following beneficial effects:

[0019] (1) The present invention utilizes the B-site doping principle of perovskite oxide and uses a simple sol-gel method to prepare SrCoO 3-δExcess Ni is precisely introduced into the system, and Sr with high OER activity is induced through pre-calcination and annealing. 9 Ni 7 O 21 Phase, Sr 9 Ni 7 O 21 phase and NiO phase, and designed a lower annealing temperature to avoid Sr 9 Ni 7 O 21 The phase decomposes at high temperature, increasing its content in the catalyst and improving the overall catalytic performance of the material.

[0020] (2) Multiphase structure SrCo prepared by the present invention 1-x Ni x O 3-δ Perovskite-type high-performance OER catalytic materials exhibit low electrochemical potentials in alkaline electrolytes. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 For preparing the multiphase structure SrCo in Example 1 1-x Ni x O 3-δ Schematic diagram of the process of perovskite-type OER catalytic materials.

[0022] Figure 2 Pure phase SrCoO prepared in Comparative Example 1 3-δ X-ray diffraction (XRD) diagram of perovskite-type catalytic material, pure phase SrCo prepared in comparative example 2 0.9 Ni 0.1 O 3-δ X-ray diffraction (XRD) patterns of perovskite-type OER catalyst materials, multiphase structure SrCo prepared in Examples 1-5 1-x Ni x O 3-δ X-ray diffraction (XRD) patterns of perovskite-type OER catalysts.

[0023] Figure 3 For the multiphase structure SrCo of Example 1-5 1-x Ni x O 3-δ Scanning electron microscope (SEM) image of perovskite OER catalyst material, pure phase SrCoO prepared in comparative example 1 3-δ Scanning electron microscope (SEM) image of perovskite-type catalytic material, pure phase SrCo prepared in comparative example 2 0.9 Ni 0.1 O 3-δ Scanning electron microscope (SEM) images of perovskite-type catalyst materials, (a) is the pure phase SrCoO prepared in Comparative Example 13-δ Scanning electron microscope (SEM) image of perovskite-type catalyst material; (b) is the pure phase SrCo prepared in Comparative Example 2 0.9 Ni 0.1 O 3-δ Scanning electron microscope (SEM) image of perovskite OER catalyst material; (c) is the multiphase structure SrCo prepared in Example 2 0.8 Ni 0.2 O 3-δ Scanning electron microscope (SEM) image of perovskite OER catalyst material; (d) is the multiphase structure SrCo prepared in Example 3 0.7 Ni 0.3 O 3-δ Scanning electron microscope (SEM) image of perovskite OER catalyst material; (e) is the multiphase structure SrCo prepared in Example 1 0.6 Ni 0.4 O 3-δ Scanning electron microscope (SEM) image of perovskite OER catalyst material; (f) is the multiphase structure SrCo prepared in Example 4 0.5 Ni 0.5 O 3-δ Scanning electron microscope (SEM) image of perovskite-type OER catalyst material.

[0024] Figure 4 The multiphase structure SrCo prepared in Example 1 1-x Ni x O 3-δ Transmission electron microscopy (TEM) images of perovskite-type OER catalyst materials, (a) multiphase structure SrCo 1-x Ni x O 3-δ Scanning transmission electron microscopy (STEM) images of perovskite-type OER catalyst materials, (b) multiphase structure SrCo 1-x Ni x O 3-δ High-resolution transmission electron microscopy (HRTEM) image of perovskite-type OER catalyst material.

[0025] Figure 5 The multiphase structure SrCo prepared in Examples 1-5 1-x Ni x O 3-δ Perovskite OER catalytic material and pure phase SrCoO prepared in Comparative Example 1 3-δ , Pure phase SrCo prepared in Comparative Example 2 0.9 Ni 0.1 O 3-δOER linear sweep voltammetry curves of perovskite-type catalyst materials in 1 mol / L KOH electrolyte; (a) is the pure phase SrCoO prepared in Comparative Example 1 3-δ Perovskite-type catalytic material, pure phase SrCo prepared in Comparative Example 2 0.9 Ni 0.1 O 3-δ Perovskite-type catalytic material, multiphase structure SrCo prepared in Examples 1-4 1- x Ni x O 3-δ OER linear sweep voltammetry curves of perovskite OER catalytic materials in 1 mol / L KOH electrolyte; (b) Multiphase structure SrCo prepared in Example 1 and Example 5 1-x Ni x O 3-δ OER linear sweep voltammetry curves of perovskite-type OER catalytic materials in 1 mol / L KOH electrolyte. DETAILED DESCRIPTION

[0026] The present invention is further described in detail below with reference to the accompanying drawings and embodiments, but the protection scope of the present invention is not limited to the described contents.

[0027] Example 1

[0028] A multiphase structure SrCo 0.6 Ni 0.4 O 3-δ The preparation method of the perovskite-type high-performance OER catalytic material specifically comprises the following steps:

[0029] (1) Weigh 4 mmol Sr(NO 3 ) 2 、2.4mmol Co(NO 3 ) 2 6H 2 O and 1.6mmol Ni(NO 3 ) 2 6H 2 O was completely dissolved in 45 mL of deionized water and placed in an oil bath and stirred at 70 °C for 30 min to obtain a pink precursor solution.

[0030] (2) Add 8 mmol of ethylenediaminetetraacetic acid and 16 mmol of citric acid as complexing agents to the precursor solution of step (1), add ammonia water dropwise to adjust the pH of the solution to 7-9 to ensure that the complexing agent is completely dissolved, then raise the temperature of the oil bath to 120° C. and continue stirring for 40-45 minutes until the solution turns into a purple-red viscous gel.

[0031] (3) The gel obtained in step (2) was transferred to a vacuum drying oven and dried at 250° C. for 6 h to obtain a black fluffy precursor.

[0032] (4) The precursor obtained in step (3) was simply ground and transferred to a muffle furnace, pre-calcined at 400°C for 2h at a heating rate of 5°C / min, then heated to 950°C and sintered for 6h. The obtained product was ground for 30-40min to obtain a dark black sample of SrCo 1-y Ni y O 3-δ , Sr 9 Ni 7 O 21 And NiO three-phase mixed structure catalyst powder.

[0033] Example 2

[0034] A multiphase structure SrCo 0.8 Ni 0.2 O 3-δ The preparation method of the perovskite-type high-performance OER catalytic material specifically comprises the following steps:

[0035] (1) Weigh 4 mmol Sr(NO 3 ) 2 、3.2mmol Co(NO 3 ) 2 6H 2 O and 0.8mmol Ni(NO 3 ) 2 6H 2 O was completely dissolved in 45 mL of deionized water and placed in an oil bath and stirred at 70 °C for 30 min to obtain a pink precursor solution.

[0036] (2) Add 8 mmol of ethylenediaminetetraacetic acid and 16 mmol of citric acid as complexing agents to the precursor solution of step (1), add ammonia water dropwise to adjust the pH of the solution to 7-9 to ensure that the complexing agent is completely dissolved, then raise the temperature of the oil bath to 120° C. and continue stirring for 40-45 minutes until the solution turns into a purple-red viscous gel.

[0037] (3) The gel obtained in step (2) was transferred to a vacuum drying oven and dried at 250° C. for 6 h to obtain a black fluffy precursor.

[0038] (4) The precursor obtained in step (3) was simply ground and transferred to a muffle furnace, pre-calcined at 400°C for 2h at a heating rate of 5°C / min, then heated to 950°C and sintered for 6h. The obtained product was ground for 30-40min to obtain a dark black sample of SrCo 1-y Ni y O3-δ , Sr 9 Ni 7 O 21 And NiO three-phase mixed structure catalyst powder.

[0039] Example 3

[0040] A multiphase structure SrCo 0.7 Ni 0.3 O 3-δ The preparation method of the perovskite-type high-performance OER catalytic material specifically comprises the following steps:

[0041] (1) Weigh 4 mmol Sr(NO 3 ) 2 、2.8mmol Co(NO 3 ) 2 6H 2 O and 1.2mmol Ni(NO 3 ) 2 6H 2 O was completely dissolved in 45 mL of deionized water and placed in an oil bath and stirred at 70 °C for 30 min to obtain a pink precursor solution.

[0042] (2) Add 8 mmol of ethylenediaminetetraacetic acid and 16 mmol of citric acid as complexing agents to the precursor solution of step (1), add ammonia water dropwise to adjust the pH of the solution to 7-9 to ensure that the complexing agent is completely dissolved, then raise the temperature of the oil bath to 120° C. and continue stirring for 40-45 minutes until the solution turns into a purple-red viscous gel.

[0043] (3) The gel obtained in step (2) was transferred to a vacuum drying oven and dried at 250° C. for 6 h to obtain a black fluffy precursor.

[0044] (4) The precursor obtained in step (3) was simply ground and transferred to a muffle furnace, pre-calcined at 400°C for 2h at a heating rate of 5°C / min, then heated to 950°C and sintered for 6h. The obtained product was ground for 30-40min to obtain a dark black sample of SrCo 1-y Ni y O 3-δ , Sr 9 Ni 7 O 21 And NiO three-phase mixed structure catalyst powder.

[0045] Example 4

[0046] A multiphase structure SrCo 0.5 Ni 0.5 O 3-δThe method for preparing a perovskite-type high-performance OER catalytic material specifically comprises the following steps:

[0047] (1) Weigh 4 mmol Sr(NO 3 ) 2 、2mmol Co(NO 3 ) 2 6H 2 O and 2mmol Ni(NO 3 ) 2 6H 2 O was completely dissolved in 45 mL of deionized water and placed in an oil bath and stirred at 70 °C for 30 min to obtain a pink precursor solution.

[0048] (2) Add 8 mmol of ethylenediaminetetraacetic acid and 16 mmol of citric acid as complexing agents to the precursor solution of step (1), add ammonia water dropwise to adjust the pH of the solution to 7-9 to ensure that the complexing agent is completely dissolved, then raise the temperature of the oil bath to 120° C. and continue stirring for 40-45 minutes until the solution turns into a purple-red viscous gel.

[0049] (3) The gel obtained in step (2) was transferred to a vacuum drying oven and dried at 250° C. for 6 h to obtain a black fluffy precursor.

[0050] (4) The precursor obtained in step (3) was simply ground and transferred to a muffle furnace, pre-calcined at 400°C for 2h at a heating rate of 5°C / min, then heated to 950°C and sintered for 6h. The obtained product was ground for 30-40min to obtain a dark black sample of SrCo 1-y Ni y O 3-δ , Sr 9 Ni 7 O 21 And NiO three-phase mixed structure catalyst powder.

[0051] Example 5

[0052] A multiphase structure of SrCo 0.6 Ni 0.4 O 3-δ The method for preparing a perovskite-type high-performance OER catalytic material specifically comprises the following steps:

[0053] (1) Weigh 4 mmol Sr(NO 3 ) 2 、2.4mmol Co(NO 3 ) 2 6H 2 O and 1.6mmol Ni(NO 3 ) 2 6H2 O was completely dissolved in 45 mL of deionized water and placed in an oil bath and stirred at 70 °C for 30 min to obtain a pink precursor solution.

[0054] (2) Add 8 mmol of ethylenediaminetetraacetic acid and 16 mmol of citric acid as complexing agents to the precursor solution of step (1), add ammonia water dropwise to adjust the pH of the solution to 7-9 to ensure that the complexing agent is completely dissolved, then raise the temperature of the oil bath to 120° C. and continue stirring for 40-45 minutes until the solution turns into a purple-red viscous gel.

[0055] (3) The gel obtained in step (2) was transferred to a vacuum drying oven and dried at 250° C. for 6 h to obtain a black fluffy precursor.

[0056] (4) The precursor obtained in step (3) was simply ground and transferred to a muffle furnace, pre-calcined at 400°C for 2h at a heating rate of 5°C / min, then heated to 1050°C and sintered for 6h. The obtained product was ground for 30-40min to obtain a dark black sample of SrCo 1-y Ni y O 3-δ 、Trace Sr 9 Ni 7 O 21 Catalyst powder with a three-phase mixed structure of NiO.

[0057] Comparative Example 1:

[0058] Preparation of multiphase structure SrCo by comparative example 1 and example 1 of the present invention 1-x Ni x O 3-δ Compared with the preparation method of perovskite-type high-performance OER catalytic material, the difference is that the molar ratio of Sr element, Co element and Ni element in the weighed raw materials is 1:1:0.

[0059] Comparative Example 2:

[0060] Preparation of multiphase structure SrCo by comparative example 1 and example 1 of the present invention 1-x Ni x O 3-δ Compared with the preparation method of perovskite-type high-performance OER catalytic material, the difference is that the molar ratio of Sr element, Co element and Ni element in the weighed raw materials is 1:0.9:0.1.

[0061] Effect example

[0062] according to Figure 2 Multiphase structure SrCo 1-x Ni x O 3-δX-ray diffraction (XRD) patterns of perovskite-type high-performance OER catalysts. Figure 4 Multiphase structure SrCo 1-x Ni x O 3-δ The transmission electron microscope (TEM) images of the perovskite-type high-performance OER catalyst material show that Examples 1-5 are a multiphase structure of SrCo 1-x Ni x O 3-δ Perovskite-type high-performance OER catalyst material is SrCo 1- y Ni y O 3-δ , Sr 9 Ni 7 O 21 and NiO multiphase mixed structure; Comparative Example 1 is pure phase SrCoO 3-δ Perovskite-type catalytic material, comparative example 2 is pure phase SrCo 0.9 Ni 0.1 O 3-δ Perovskite-type high-performance OER catalytic materials; Figure 2 Compared with Example 1, Example 5 shows that when the final sintering temperature of the current body is increased from 950°C to 1050°C, Sr 9 Ni 7 O 21 The content of the phase decreased significantly, and the content of the NiO phase increased significantly.

[0063] from Figure 3 Multiphase structure SrCo 1-x Ni x O 3-δ The scanning electron microscope (SEM) images of the perovskite-type high-performance OER catalyst materials show that the multiphase structure SrCo prepared in Examples 1-4 1-x Ni x O 3-δ The preparation method of perovskite-type high-performance OER catalytic materials, as the Ni content increases, the particle size of the catalyst powder continues to decrease, and the surface pores gradually increase, which is conducive to exposing more active sites during the catalytic process.

[0064] from Figure 5 It can be seen from the OER linear sweep voltammetry curves that the multiphase structure SrCo prepared in Examples 1-5 of the present invention 1- x Ni x O 3-δ Perovskite-type high-performance OER catalyst material with a performance of 10 mA cm in 1 mol / L KOH electrolyte -2The overpotential values ​​under the current density are 321mV, 365mV, 347mV, 338mV, and 372mV respectively. 3-δ Perovskite-type catalytic material and pure phase SrCo prepared in Comparative Example 2 0.9 Ni 0.1 O 3-δ Perovskite-type high-performance OER catalyst material with a performance of 10 mA cm in 1 mol / L KOH electrolyte -2 The overpotential values ​​under current density are 419mV and 382mV respectively. Since the overpotential in the catalytic material is an important parameter for evaluating its catalytic performance, it is concluded that the multiphase structure SrCo 1-x Ni x O 3-δ In the preparation method of perovskite-type high-performance OER catalytic material, when the molar ratio of Sr, Co and Ni is 1:0.6:0.4, the overpotential is as low as 321mV, which has the best OER catalytic performance. At the same time, the active source of the sample is mainly Sr. 9 Ni 7 O 21 The presence and content of phases.

Claims

1. A multiphase structure SrCo 1-x Ni x O 3-δ A method for preparing a perovskite-type OER catalytic material, characterized in that: The following steps are involved: (1) Weigh Sr(NO3)2, Co(NO3)2·6H2O and Ni(NO3)2·6H2O in a certain molar ratio, add water to dissolve to form a mixed solution and heat it; (2) After adding the complexing agent, ammonia water is added to adjust the pH of the solution to alkaline, and the water is evaporated by heating to obtain a gel; The gel was then vacuum dried, pre-calcined and annealed to obtain SrCo 1-x Ni x O 3-δ Catalyst, wherein 0.2≤x≤0.5, and δ is 0.2-0.

5.

2. The multiphase structure SrCo according to claim 1 1-x Ni x O 3-δ A method for preparing a perovskite-type OER catalytic material, characterized in that: The molar ratio of Sr(NO3)2, Co(NO3)2·6H2O and Ni(NO3)2·6H2O in step (1) is 1:1-x:x, 0.2≤x≤0.

5.

3. The multiphase structure SrCo according to claim 1 1-x Ni x O 3-δ A method for preparing a perovskite-type OER catalytic material, characterized in that: The heating temperature in step (1) is 70-80° C. and the heating time is 20-30 min.

4. The multiphase structure SrCo according to claim 1 1-x Ni x O 3-δ A method for preparing a perovskite-type OER catalytic material, characterized in that: In the step (2), the complexing agents are ethylenediaminetetraacetic acid and citric acid, wherein the molar ratio of ethylenediaminetetraacetic acid, citric acid, and total metal ions is (0.8-1.2):(1.8-2.2):

1.

5. The multiphase structure SrCo according to claim 1 1-x Ni x O 3-δ A method for preparing a perovskite-type OER catalytic material, characterized in that: The pH of the solution in step (2) is 7-9, the heating temperature is 110-120° C., and the heating time is 40-45 min.

6. The multiphase structure SrCo according to claim 1 1-x Ni x O 3-δ A method for preparing a perovskite-type OER catalytic material, characterized in that: In the step (2), the vacuum drying temperature is 220-250°C, and the vacuum drying time is 5-6 hours; the pre-calcination temperature is 300-400°C, and the calcination time is 2-3 hours, and the heating rate is 5°C / min.

7. The multiphase structure SrCo according to claim 1 1-x Ni x O 3-δ A method for preparing a perovskite-type OER catalytic material, characterized in that: In the step (2), the annealing treatment temperature is 950-1050° C. and the time is 5-6 hours.

8. The multiphase structure SrCo according to any one of claims 1 to 7 1-x Ni x O 3-δ Preparation method of perovskite-type OER catalyst material to prepare multiphase structure SrCo 1-x Ni x O 3-δ Perovskite-type OER catalytic materials.

9. The multiphase structure SrCo according to claim 8 1-x Ni x O 3-δ Perovskite-type OER catalytic material, characterized in that The multiphase structure of SrCo 1-x Ni x O 3-δ Perovskite-type OER catalytic materials include SrCo 1-y Ni y O 3-δ Phase, Sr9Ni7O 21 phase and NiO phase, y is 0.1-0.2.

Citation Information

Patent Citations

  • Cation co-doped perovskite catalyst for oxygen evolution reaction and preparation method thereof

    CN110860292A